The Mediating Role of Digital Tax Literacy in TikTok-Based Tax Compliance Among Indonesian Taxpayers - Muhammad Rinaldi; Muhammad Harits Zidni Khatib Ramadhani; Melda Aulia Ramadhani; Sitti Rahma Sudirman; Muhamad Amir Ariandi (FAKULTAS DAKWAH UIN SALATIGA, 2025)
The digital transformation of tax administration has prompted tax authorities to utilize social media as a tool for education and communication, including platforms such as TikTok. This study aims to examine the effect of perceived information quality on digital tax compliance, with digital tax literacy serving as a mediating variable. Employing a quantitative explanatory approach and purposive sampling technique, data were collected through an online questionnaire distributed to taxpayers who are active TikTok users. The results show that perceived information quality does not have a direct effect on digital tax compliance but has a positive effect on digital tax literacy. Furthermore, digital tax literacy positively influences digital tax compliance and fully mediates the relationship between perceived information quality and digital tax compliance. These findings highlight the crucial role of digital literacy as a prerequisite for the effectiveness of tax communication through social media.